The influence of socio‐economic status on child temperament and psychological symptom profiles. - Hong, Ryan Y.; Ding, Xiao Pan; Chan, Kelly M. Y.; Yeung, Wei‐Jun Jean (British Journal of Psychology, 2024)
The influence of socio‐economic status (SES) on child temperament and psychological symptoms was examined using a nationally representative sample in Singapore. Data were available for 2169 children from 1987 families. Caregivers' reports were obtained on children aged 4–6. SES was operationalized as an aggregation of household income per capita, parental education level and housing type. Compared to their counterparts from higher SES families, children from low‐SES families tended to exhibit (a) higher negative affectivity but lower effortful control, and (b) higher internalizing and externalizing symptoms. In addition, children with a 'resilient' temperamental profile (i.e. low negative affectivity and high effortful control) were more likely to come from families with much higher SES, relative to children with other profiles. Children with high internalizing symptoms tended to come from low‐SES backgrounds, regardless of their externalizing symptoms. Among children with low internalizing symptoms, those with high externalizing symptoms came from lower SES backgrounds compared to those with low externalizing symptoms. Parental warmth and distress mediated the association between SES and child temperament and symptom profiles, with the exception of distress in the SES–temperament link. These findings supported the family stress model and highlighted the novel perspective of SES's influence on configurations of child temperament and symptom characteristics.